2015
DOI: 10.1016/j.molcel.2015.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Melanoma Cells with Distal Keratinocytes Trigger Metastasis via Notch Signaling Inhibition of MITF

Abstract: The most critical stage in initiation of melanoma metastasis is the radial to vertical growth transition, yet the triggers of this transition remain elusive. We suggest that the microenvironment drives melanoma metastasis independently of mutation acquisition. Here we examined the changes in microenvironment that occur during melanoma radial growth. We show that direct contact of melanoma cells with the remote epidermal layer triggers vertical invasion via Notch signaling activation, the latter serving to inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 39 publications
2
79
0
Order By: Relevance
“…Thus, it has been shown that MITF interferes with production of MT1-MMP (19) or transcriptional activation of miR222/221 (42), a microRNA that is capable of invasion initiation in melanoma cells (43). Additionally, two papers reported different pathways through which MITF suppresses the activity of Rho-associated coiled-coil containing protein kinase 1 (ROCK1) (19, 20), an important regulator of tumor cell invasion (44) acting downstream of small GTPase RHO-A.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been shown that MITF interferes with production of MT1-MMP (19) or transcriptional activation of miR222/221 (42), a microRNA that is capable of invasion initiation in melanoma cells (43). Additionally, two papers reported different pathways through which MITF suppresses the activity of Rho-associated coiled-coil containing protein kinase 1 (ROCK1) (19, 20), an important regulator of tumor cell invasion (44) acting downstream of small GTPase RHO-A.…”
Section: Discussionmentioning
confidence: 99%
“…4D). Remarkably, noninvasive melanoma cells (Golan et al 2015) acquired significant invasion ability upon KIT overexpression ( Fig. 4G; Supplemental Fig.…”
Section: Enhancer Methylation Plasticity In Tumorigenesismentioning
confidence: 94%
“…Fortyeight hours post-transfection, an invasion assay was performed as previously described (Golan et al 2015).…”
Section: Invasion Assaymentioning
confidence: 99%
“…51 MITF recruits RBPJK as a cofactor in repressing transcription of microRNAs miR-221 and miR-222 in human melanoma cell lines. 52 It remains mechanistically unclear how MITF represses target genes and what functional roles MITF has through repressing gene expression.…”
Section: Mitf Target Genesmentioning
confidence: 99%